Aggression following acquired brain injury in a forensic hospital: the assessment of triggers and management strategies - Whitwham, Stephanie (2020)
Background: Aggression can often occur in people who have an Acquired Brain Injury (ABI), and the prevalence of ABI in forensic settings is high. This thesis aimed to explore aggression following ABI, how aggression is measured in various clinical settings, and then how aggression is defined, triggered and managed in a forensic hospital setting.